돼지고기 속성별 소비자 선호도 분석 - 지인배 (한국농촌경제연구원, 2012)
The purpose of this study is to analyze the preference of consumers for pork using conjoint analysis. The study estimates the price of pork which consumers are willing to pay depending on the attributes of pork and forecasts the market share of pork pursuant to full implementation of FTA using the result of the estimate. The summary of the result of analysis revealed that when consumers purchase pork, they have the highest willingness to pay for the freshness among various attributes of pork (i.e., country of origin, the type of storage, freshness, brand), followed by country of origin, the type of storage, and brand in that order. The price which consumers were willing to pay for domestic pork was higher by 1,058 won over the price for imported pork. The result of forecast on market share showed that the market share of domestic pork after 2012 would maintain the level of approximately 60~70%. Accordingly, we will have to put focus on the supply of fresh domestic pork in order to sustain the level of existing market share.
Keywords: 돼지고기; 컨조인트 분석; 소비자 선호; pork; conjoint analysis; consumers' preference